Sputum Quality Assessment Regarding Sputum Culture for Diagnosing Lower Respiratory Tract Infections in Children - Popova, Gorica (Open Access Maced J Med Sci, 2019)
BACKGROUND: The clinical relevance of specimens from the lower airways is often debatable. However, they are most commonly examined for diagnosing lower respiratory tract infections (LRTIs). AIM: This study aimed to determine the diagnostic value of sputum quality assessment about sputum culture for diagnosing LRTIs in children. METHODS: In six months, a total of 1485 sputum samples were quality assessed by using Bartlett’s grading system. All samples, regardless of their quality, were cultured, identified, and antimicrobial susceptibility testing was performed by Kirby-Bauer disc-diffusion method. RESULTS: Among the acceptable category, defined by Bartlett’s grading system, 132 (63.2%) samples showed culture positivity of which Streptococcus pneumoniae 48 (36.4%) was most commonly isolated, followed by Moraxella catarrhalis 22 (16.7%) and Haemophilus influenza 21 (15.9%). Among the non-acceptable category, 185 (14.5%) samples were culture positive of which most commonly isolated were Escherichia coli, Staphylococcus aureus and Pseudomonas aeruginosa with 64 (34.6%), 54 (29.2%) and 28 (15.1%), respectively. CONCLUSION: Sputum quality assessment is a useful tool for distinguishing the true respiratory pathogens from possible colonising flora for which antibiotic treatment should not be highly considered.